Uniaxial compressive stress–strain relationship of mixed recycled aggregate concrete. (3rd October 2022) - Yan, Pengpeng; Wu, Jin; Lin, Dadi; Liu, Xu
Highlights: This study aims to investigate the uniaxial stress–strain relation of mixed recycled aggregate concrete (MRC). The stress–strain relation of MRC cannot be well predicted by existing models. The proposed model can effectively predict the stress–strain relation of MRC. Abstract: The purpose of this paper is to study the uniaxial stress–strain relationship of mixed recycled concrete (MRC), which composed of brick recycled aggregate (BRA), concrete recycled aggregate (CRA) and natural aggregate (NA). MRC with various replacement ratio of MRA and various contents of BRA was studied under uniaxial compression. The stress–strain characteristic and toughness of MRC were studied firstly, and the results exhibited that the peak stress and elastic modulus decreased with the increase of MRA replacement ratio and BRA content, while the opposite trend was observed for the ultimate and peak strain. Then, the test stress–strain data were compared with existing stress–strain models of natural or recycled concrete. The comparison results indicate that the existing models cannot be well predicted the stress–strain relationship of MRC. According to the test results in this study, the stress–strain constitutive model of MRC was established by modifying of the shape parameters for the CRA concrete (RAC) constitutive model, which can well predict the stress–strain relationship of MRC.